2024
DOI: 10.3389/fpsyg.2023.1305828
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Internet addiction and body mass index and the predictive role of emotion dysregulation

Morteza Azizi,
Behrouz Abbasi,
Hajar Aghaei

Abstract: In recent years, the widespread use of the Internet has led to increasing concerns about problematic behaviors related to excessive Internet use and their potential consequences. This study aimed to investigate the relationship between Internet addiction (IA), body mass index (BMI), and emotion dysregulation (ED). Specifically, the study aimed to determine if IA significantly predicts obesity and if both Internet addiction and obesity can be significantly predicted by ED. 367 school-attending adolescents (Mage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Fourth, we did not collect data on all the variables that could be related to IA, such as the purpose of Internet use and medical conditions, including medications. Fifth, previous studies have shown that, there is a positive relationship between internet addiction and obesity (49,50). However, due to the sample size of the subjects, the correlation between internet addiction and obesity in this study did not reach a significant level, which requires further research in the future.…”
Section: Discussionmentioning
confidence: 53%
“…Fourth, we did not collect data on all the variables that could be related to IA, such as the purpose of Internet use and medical conditions, including medications. Fifth, previous studies have shown that, there is a positive relationship between internet addiction and obesity (49,50). However, due to the sample size of the subjects, the correlation between internet addiction and obesity in this study did not reach a significant level, which requires further research in the future.…”
Section: Discussionmentioning
confidence: 53%
“…Further research in the area. Excessive internet use in adolescents has been associated with emotion dysregulation, internet addiction, increased BMI levels, and symptoms of social anxiety [ 65 , 66 ]. Physical activity would be helpful for internet addiction for university students, by increasing coping styles [ 67 ].…”
Section: Recommended Strategies For Enhancing Treatment Outcomes and ...mentioning
confidence: 99%